2019
DOI: 10.14742/ajet.4432
|View full text |Cite
|
Sign up to set email alerts
|

Habit and hedonic motivation are the strongest influences in mobile learning behaviours among higher education students in Malaysia

Abstract: Mobile learning has become a common experience in higher education and in the professional workforce. However, the readiness of accounting students to engage in such learning appears to be weaker than in other disciplines. Therefore, this study set out to identify the factors affecting accounting students’ behavioural intention (BI) to accept mobile learning. The participants of this study were 358 accounting students of public universities in Malaysia. The study  was anchored in the unified theory of acceptan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
106
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 61 publications
(81 reference statements)
16
106
5
Order By: Relevance
“…According to another finding of this study, HB had a significant influence on actual usage and behavioral intention to use BL. This was in line with the research of Tarhni (2017) (27) and Moorthy et al (2017) (32). Venkatesh et al (2012) (25) revealed that routine use of a technology plays an important role in its adoption.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…According to another finding of this study, HB had a significant influence on actual usage and behavioral intention to use BL. This was in line with the research of Tarhni (2017) (27) and Moorthy et al (2017) (32). Venkatesh et al (2012) (25) revealed that routine use of a technology plays an important role in its adoption.…”
Section: Discussionsupporting
confidence: 87%
“…SI is defined as "the degree to which an individual perceives that important others (such as peers and faculty members) believe he or she should use the modern system or new approach in learning" (21). Several studies have shown that SI has a significant influence on the behavioral intention of adopting a system (17,31,32). H3: SI will have a significant influence on students' behavioral intention to use BL…”
Section: Social Influence (Si)mentioning
confidence: 99%
See 3 more Smart Citations